A revision of Festuca (Loliinae, Pooideae, Poaceae) in Chile - Ospina, Juan Camilo; Aliscioni, Sandra Silvina; Denham, Silvia Suyai (Phytotaxa, 2015)
The new combination and new variety Festuca acanthophylla. A taxonomic revision of the genus Festuca in Chile is presented based on morphological and anatomical data. We recognize 19 species and two varieties in Chile. We propose eight new synonyms. Lectotypes are designated for the names Diplachne brevifolia, F. gracillima fo. scabra, F. gracillima var. ramosa, F. orthophylla var. boliviana, F. ovina subvar. pubiscula, F. ovina var. wilczekii, F. purpurascens fo. aristata, F. purpurascens var. submutica, F. rubra subsp. corcovadensis, and F. saltana. Second-step lectotypes are designated for the names F. berteroniana, F. davillae, F. desvauxii, F. dumetorum, F. erecta, F. hypsophila, F. insularis, F. lechleriana, F. monticola, F. orthophylla var. meyenii, F. pascua, F. platyphylla, F. robusta, F. subandina, F. thermarum, and F. tunicate. Specimens erroneously indicated as “typus” (holotype) in the literature are corrected to lectotype for the names Diplachne rigescens, F. acuta, F. asperata, F. cavillieri, F. commersonii, F. glaucophylla, F. gracillima, F. gracillima var. patagonica, F. kurtziana, F. magellanica, F. neuquenensis var. parodiana, F. ovina subsp. hystricola, F. ovina var. antarctica, F. purpurascens, F. serranoi, F. steudelii, and Poa argentina. A key to all Chilean species, distribution data, illustrations, and leaf blade anatomical and micromorphological descriptions are also provided. The new combination and new variety Festuca acanthophylla var. scabriuscula is proposed.